Comparison of the performance characteristics of the tonpilz transducers fabricated from 0.60PMN-0.40PT & PZT piezoceramics - Yalcin, Ezgi; Ankut, Merve; Sungur, Sena M.; Turgut, H. Ibrahim; Kar, K. Sueda; Alkoy, Sedat; Aykac, Aykut (Taylor & Francis Ltd, 2021)
In this study, tonpilz transducers based on 0.60Pb(Mg1/3Nb2/3)O-3-0.40PbTiO(3) (60PMN-PT) and commercially available lead zirconate titanate (PZT) compositions (PZT 4, PZT 5H, PZT 8 and PZT 5A) were designed, fabricated, characterized and compared for their underwater performance. Each stack is composed of two rings of PZT or PMN-PT ceramics. Transducers were designed and analyzed using the commercial ATILA finite elements analysis (FEA) code. Commercially available powders were used for PZT, whereas 60PMN-PT powders with pure perovskite phase were synthesized using solid-state reaction route. Ceramic rings have been produced using dry pressing. Dielectric, piezoelectric and electromechanical properties of the rings were calculated using the resonance method. Vibration modes of the rings and transducers constructed from various types of piezoceramics were analyzed using FEA. The main resonance frequency of the tonpilz transducer belonging to the longitudinal piston mode was measured in the mid-frequency range between 30 and 35 kHz. Underwater acoustic measurements were conducted on polymer-coated transducers, and their performances were compared for possible underwater acoustic applications. Transducers fabricated from 60PMN-PT were found to have comparable underwater performance with that of PZT 4, where the Transmitting Voltage Response (TVR) reached 135 - 136 dB re 1 mu Pa/V @1 m range with a -3dB bandwidth of 4 kHz. These results indicated the viability of using 60PMN-PT ceramics in active device applications in an array form.
Keywords: Piezoelectricity; tonpilz transducer; PMN-PT; PZT; FEA